2012
DOI: 10.1590/s0101-60832012000500004
|View full text |Cite
|
Sign up to set email alerts
|

Beber e dirigir: características de condutores com bafômetro positivo

Abstract: Contexto:O beber e dirigir não foi su cientemente estudado no Brasil até agora. Objetivo: Apresentar dados do primeiro levantamento sobre o comportamento do beber e dirigir de um estado do Brasil. Método: Foram conduzidas 1.799 entrevistas anônimas com motoristas em postos de checagem de sobriedade em 10 cidades, representando as 10 regiões geográ cas do estado de Minas Gerais. Desses motoristas, 1.209 (67,2%) responderam a um questionário estruturado e aceitaram o teste do bafômetro. Resultados: Vinte por cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
2
6
1
5
Order By: Relevance
“…These results differ from the majority of studies conducted in more developed countries, which have shown a greater likelihood of this behavior in young adults [39,44]. However, investigations conducted in Brazil have shown a tendency consistent with the present study's results, which indicate a greater likelihood of DUIA in drivers aged 30 years and older [21,45]. This may reflect the lesser availability of automobiles to younger drivers in Brazil and some macroregions [26].…”
Section: Discussioncontrasting
confidence: 98%
“…These results differ from the majority of studies conducted in more developed countries, which have shown a greater likelihood of this behavior in young adults [39,44]. However, investigations conducted in Brazil have shown a tendency consistent with the present study's results, which indicate a greater likelihood of DUIA in drivers aged 30 years and older [21,45]. This may reflect the lesser availability of automobiles to younger drivers in Brazil and some macroregions [26].…”
Section: Discussioncontrasting
confidence: 98%
“…Trauma due to traffic accidents, for example, account for 9.4 and 9.0 of deaths or disabilities, respectively, and are associated with acute consumption in the Americas. These data corroborate with the characteristics of individuals victims of the fatal combination between alcohol and driving vehicles, which international research describe to be more frequent during the period from 6 p.m. to 6 a.m. on weekends and among young individuals (19 to 39 years) of the male sex (OPS, 2015;Campos et al, 2012).…”
Section: The Problemsupporting
confidence: 82%
“…Studies confirm that, with respect to sociodemographic characteristics, men are more likely to violate traffic laws, 16 drive at a high rate of speed, 17 drive under the influence of alcohol, 18,19 and repeat such behaviors, 20 ultimately becoming involved in crashes. Similarly, young people have a higher prevalence of driving after drinking alcohol and being a passenger of a driver who drank alcohol.…”
Section: Discussionmentioning
confidence: 94%